The Effectiveness of Behavioristic Individual Counseling with an Operant Conditioning Technique to Improve Study Attitudes and Study Habits in Students - Safitri, Noer; Sugiyo, Sugiyo; Awalya, Awalya (Universitas Negeri Semarang, 2022)
Study attitudes and study habits are important in education because they determine the success of learning. These became the problems in this research because low study attitudes and study habits will cause the decline in students’ academic achievement, so a solution is needed. In dealing with this issue, the present research examined the effectiveness of behavioristic individual counseling with an operant conditioning technique to improve the study attitudes and study habits of the ninth graders at SMP Negeri 13 Semarang. It was experimental research which used a randomized pretest posttest comparison group design. In addition, a manova analysis was done to both experimental and control groups. In detail, the treatment used in this study could improve students’ study attitudes and study habits. Finally, school counselors are recommended to provide a reinforcement program to support the implementation of the behavioristic individual counseling with an operant conditioning technique.